Tb(HSO4)(SO4) – a green emitting hydrogensulfate sulfate with second harmonic generation response. Issue 43 (21st October 2019) - Netzsch, Philip; Bariss, Harijs; Bayarjargal, Lkhamsuren; Höppe, Henning A.
Abstract : Green emitting Tb(HSO4 )(SO4 ) crystallises in the non-centrosymmetric space group P 21 and represents a new sulfate non-linear optical material with a SHG response comparable to KH2 PO4 (KDP). Abstract : Recently, sulfates have attracted attention as materials for non-linear optical applications. This compound class is extended by Tb(HSO4 )(SO4 ), which is solvothermally synthesised from Tb4 O7 and sulfuric acid. The compound crystallises in the non-centrosymmetric space group P 21 ( Z = 2, a = 665.03(5) pm, b = 659.41(5) pm, c = 680.24(5) pm, and β = 104.640(2)°) and is homeotypic with Ni2 In. The terbium ions adopt the indium sites and the sulfate and hydrogen sulfate anions are situated on the nickel sites. The compound shows green luminescence based on f–f-transitions and the positions of the f–d-excitation bands reveal a weak coordination behaviour of the sulfate anions. Tb(HSO4 )(SO4 ) exhibits a second harmonic generation response comparable to KH2 PO4 (KDP). Furthermore, the material is characterised by electrostatic calculations, infrared spectroscopy and thermal analysis.